Prevention of endodontic infections: A public health perspective on reducing disease burden and promoting oral health – A narrative review - Ahmed Abdulaziz Almohammadi (Saudi Endodontic Journal, 2026)
Abstract Endodontic infections, resulting primarily from untreated dental caries, represent a significant global public health challenge affecting billions worldwide. Despite being largely preventable through evidence-based interventions, endodontic infections continue to impose substantial disease burden and healthcare costs. This narrative review aims to examine current evidence on prevention strategies for endodontic infections from a public health perspective, analyze their effectiveness in reducing disease burden, and provide recommendations for integrating these strategies into comprehensive oral health programs, with particular relevance to the Saudi Arabian context. A comprehensive literature search was conducted in January 2026 across PubMed/MEDLINE, Scopus, Web of Science, and Google Scholar, covering publications from January 2020 to December 2025. Initial screening identified 287 potentially relevant articles. After title and abstract review, 156 articles were selected for full-text assessment. Hand searching yielded 12 additional articles. Final inclusion comprised 89 articles providing evidence on endodontic infection prevention, epidemiology, and public health interventions. Evidence demonstrates that comprehensive prevention strategies incorporating fluoride interventions (community water fluoridation, reducing caries by ~25%), school-based programs, dental sealants, and regular dental care significantly reduce endodontic treatment needs. Endodontic infections represent largely preventable conditions amenable to population-level public health interventions through primary prevention (fluoridation, dietary modification, oral hygiene education), secondary prevention (early detection, minimal intervention dentistry), and systems-level approaches addressing social determinants of oral health. Successful implementation requires integration into comprehensive oral health programs with attention to workforce development, policy interventions, and health insurance coverage.